Socialization on Introduction of TOEFL To Improve English Skills At SMK Negeri 1 Siantar - Sidabalok, Fifi Yanti; Alhamdi, Badrussama; Sidabutar, Rimelni; Damanik, Danny Boy; Kristiani, Theresa Nanda; Herman, Herman; Panggabean, Eva Saryati (Pengabdian Masyarakat Sumber Daya Unggul, 2023)
Community Service Activities (PkM) is an activity that provides information regarding knowledge and skills in English. This socialization activity aims to introduce and provide knowledge and insight to students at SMK N 1 Siantar about the TOEFL test through a training program and the implementation of the Test of English as Foreign Language (TOEFL) which was socialized to 32 students of class 12 TKJ II which was carried out at one of the vocational schools in Siantar, namely SMK N 1 SIANTAR on December 13, 2023. There are three stages in carrying out this socialization, namely preparation, implementation and evaluation. The socialization material presented is about how to introduce TOEFL, the purpose of TOEFL, the use of TOEFL, and displays several examples of TOEFL questions. This socialization really attracted the attention of students at SMK N 1 Siantar Class 12 TKJ 2 because they are vocational students who really have to improve their English skills according to their vocation .This socialization can also increase student's motivation to study English more seriously. From the results of the socialization for the implementation of the Test of English as Foreign Language, participants gained knowledge, insight and motivation to take part in the Test of English as Foreign Language (TOEFL) to introduce the importance of TOEFL and improve students' ability to use English for future purposes